Doxycycline Injection for Sclerotherapy of Lower Eyelid Festoons and Malar Edema: Preliminary Results. Issue 5 (September 2019) - Godfrey, Kyle J.; Kally, Peter; Dunbar, Kristen E.; Campbell, Ashley A.; Callahan, Alison B.; Lo, Christopher; Freund, Robert; Lisman, Richard D.
Abstract : Purpose: To investigate the safety and efficacy of direct, intralesional doxycycline hyclate injection for improving the appearance of cosmetically significant lower eyelid festoons and malar edema. Methods: An Institutional Review Board approved, retrospective review was performed of 15 consecutive patients with malar edema and/or festoons injected with doxycycline hyclate at a concentration of 10 mg/ml. Pre- and postinjection photographs were reviewed and graded on a scale of 0 to 3 (0: no festoon; 1: small festoon; 2: medium festoon; 3: large festoon) by 2 masked physician observers. Patients were excluded from the final analysis if they received an alternate dose concentration, had incomplete photographic records, or did not follow up. Student t test was used for statistical analysis. Results: Twenty consecutive treatment areas of 11 patients were included in the analysis. Final follow up ranged from 3 to 104 weeks, with a mean follow up of 22.5 weeks. The average (standard deviation) initial festoon grade of 2.5 (0.58) decreased to 0.9 (0.82) with a p value of <0.001. The average number of injections performed per side was 1.4 (range: 1–2). The mean volume per injection was 0.72 ml (range: 0.15–2.0 ml). Commonly documented subjective complaints were burning sensation with injection, pain, bruising, and erythema. There were no other dermatologic or visual complications following treatment. Conclusions: These preliminary results suggest that intralesional injections of doxycycline hyclate at a concentration of 10 mg/ml may be an effective treatment option for cosmetically significant lower eyelid festoons and malar edema. Future prospective studies with increased patient numbers, increasing concentrations, combination therapies with local anesthetic or regional nerve blocks, and longer follow up are needed to validate these results and determine optimal injection technique. Abstract : Intralesional injection of doxycycline hyclate may improve the appearance of esthetically undesirable lower eyelid festoons and malar edema.